2016
DOI: 10.1002/chem.201600286
|View full text |Cite
|
Sign up to set email alerts
|

Histidine‐Rich Oligopeptides To Lessen Copper‐Mediated Amyloid‐β Toxicity

Abstract: Brain copper imbalance plays an important role in amyloid-β aggregation, tau hyperphosphorylation, and neurotoxicity observed in Alzheimer's disease (AD). Therefore, the administration of biocompatible metal-binding agents may offer a potential therapeutic solution to target mislocalized copper ions and restore metallostasis. Histidine-containing peptides and proteins are excellent metal binders and are found in many natural systems. The design of short peptides showing optimal binding properties represents a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…25,95 Therefore, the design of peptide-or peptidomimeticbased metal chelators/sequestrators has been an active area of research, although most of the reported chelators lack multifunctional features. 96,97 We developed the multifunctional peptidomimetic P6 by conjugating the copper-chelating natural tripeptide Gly-His-Lys (GHK) found in humans and the peptoid-based Ab aggregation modulator P5 (Fig. 7a and b).…”
Section: Targeting Ab and Tau Aggregationmentioning
confidence: 99%
“…25,95 Therefore, the design of peptide-or peptidomimeticbased metal chelators/sequestrators has been an active area of research, although most of the reported chelators lack multifunctional features. 96,97 We developed the multifunctional peptidomimetic P6 by conjugating the copper-chelating natural tripeptide Gly-His-Lys (GHK) found in humans and the peptoid-based Ab aggregation modulator P5 (Fig. 7a and b).…”
Section: Targeting Ab and Tau Aggregationmentioning
confidence: 99%
“…Possible configurations were built considering the information obtained from NMR experiments, [48] which indicated that the probable coordinating sites are the N term ,H is1, His3, and N À from the deprotonated amide of the backboneo rt he Of rom the carbonyl group of the backbone. Possible configurations were built considering the information obtained from NMR experiments, [48] which indicated that the probable coordinating sites are the N term ,H is1, His3, and N À from the deprotonated amide of the backboneo rt he Of rom the carbonyl group of the backbone.…”
Section: Electrochemical Properties Of Cu II -Tripeptidesmentioning
confidence: 99%
“…To determine which coordination mode provides the electrochemicalp roperties observed for these complexes,a nd to assessh ow much different coordination environments would influence the electrochemical behaviour,D FT (B3LYP-D3) calculationsw erec arried out for differentc onfigurations. Possible configurations were built considering the information obtained from NMR experiments, [48] which indicated that the probable coordinating sites are the N term ,H is1, His3, and N À from the deprotonated amide of the backboneo rt he Of rom the carbonyl group of the backbone. Since minor differences are expected among the two complexes, the exploration of different binding modes was first investigated for Cu II -HAH.F ourm ajor configurations werec onsidered from ac omputationalp oint of view: 1) configuration 1,i nvolving the N term ,H is1, His3, the carboxylate group, and the carbonyl Oo fA la2;2 )configuration 2,i nvolvingt he N term ,d eprotonated amide, the carbonyl Oo fA la2, and His3; 3) configuration 3,c orresponding to the ATCUN motif (see Scheme 1) and involving the N term ,H is3, andt he two deprotonated Na mides;a nd finally,4 )configuration 4,w ith His1, His3, the deprotonated N À amide, and the carbonyl Oo f Ala2 as binding sites.…”
Section: Electrochemical Properties Of Cu II -Tripeptidesmentioning
confidence: 99%
“…However, in a longer 52-week trial, PBT2 did not reduce plaque burden or improve cognitive function to a statistically significant extent. Recently, Caballero and co-workers have designed peptide fragments containing one to two histidine residues which showed higher affinity for Cu 2+ ions than the Aβ40 peptide, and also showed reduced amyloid toxicity and reduced copper-generated ROS (Caballero et al 2016 ) (Fig. 3 i).…”
Section: Part 4: Metal Ionsmentioning
confidence: 99%
“…
Fig. 3 Proposed molecules targeting Aβ aggregation: a heparin-based N-acetyl-glucosamine monosaccharide (Kisilevsky et al 2003 ); b Enoxaparin, a low-molecular-weight heparin (Bergamaschini et al 2004 ); c RNA aptamer β55 (Ylera et al 2002 ), with bases colored as shown; d RNA aptamer E2 (Rahimi et al 2009 ); e the statin Atorvastatin (Lipitor); f doxcosahexaenoic acid (DHA); g clioquinol; h PBT2; i tripeptide H-W-H (Caballero et al 2016 )
…”
Section: Introduction: What’s In a Plaque?mentioning
confidence: 99%